Dose Escalation of Lobaplatin Concurrent with IMRT for the Treatment of Stage III-IVb NPC: A Phase I Clinical Trial - Si-Yang Wang; Xi-Wei Xu; Ji-Jin Yao; Pei-Jian Peng; Bin Zhou; Qiao-Dan Liu; Xiao-Ping Huang; Zhong Lin (Translational Oncology, 2018)
The maximum tolerated dose (MTD) of lobaplatin as a single agent chemotherapy concurrent with intensity-modulated radiotherapy (IMRT) in Asian population with nasopharyngeal carcinoma (NPC) remains unclear. From June 2016 to December 2017, 17 patients diagnosed with stage III-IVb NPC from an Asian population were prospectively enrolled. Patients were administered lobaplatin with 25-50 mg/m2 escalation of dosage on day 1. Every 21 days (days 1, 22, and 43) during radiotherapy, cycles were repeated. We administered radiotherapy as 2.12-2.27 Gy per fraction with five daily fractions each week for 6 to 7 weeks. The evaluation of lobaplatin-related toxic effects was based on the Common Terminology Criteria for Adverse Events version 4.0. During the weekly treatment period, complete blood counts and biochemistry were performed. Dose-limiting toxicities (DLTs) were determined by the following events during any cycle in which lobaplatin was administered. Each dose group consisted of at least three cases. We proceeded to the subsequent dose group in the absence of DLT with a dose increment of 5 mg/m2 until DLT occurred. Periods from 1 week prior to the chemotherapy initiation to 3 weeks after the last chemotherapy were defined as DLT observation periods. MTD was determined by the dose that was immediately below the dose that produced DLT. After analysis, DLT occurred in three patients, including a group with two of three patients in 45 mg/m2 lobaplatin and another group with one of five patients in 40 mg/m2 lobaplatin. No grade 3-4 toxicity was observed in patients treated with lobaplatin <40 mg/m2. The tumor response rate at 12 weeks after treatment was 100%. In summary, lobaplatin concurrent with IMRT was active in stage III-IVb NPC, and the MTD for the lobaplatin as single-agent chemotherapy was 40 mg/m2 when combined with IMRT in an Asian population. This trial is registered with ClinicalTrials.gov, number NCT03188497.